Effect of doping nanoparticles on the output force performance of chitosan-based nanocomposite gel actuator. Issue 9 (13th June 2019) - Zhao, Gang; Wang, Zhijie; Wang, Haojun; Zhao, Honghao; Fu, Yu; Yang, Junjie
ABSTRACT: In this work, a kind of bio-inspired chitosan-based Nanocomposite Gel Actuator (NGA) was developed whose electrolyte membrane was fabricated by doping multi-walled carbon nanotubes (MCNT). Furthermore, the output force performance of NGA was studied. The results illustrated that doping MCNT particles will play a crosslinking role. The electrolyte membrane with different MCNT doping ratios could significantly reduce its elastic modulus and enhanced its specific capacitance. When the MCNT doping ratio was 2 wt%, the output performance of the electric actuator was the best and the output force density (19.17 mN/g) and strain (0.83 %) were increased by 92% and 17%, respectively. Graphical Abstract: